Efficacy, safety, tolerability and pharmacokinetics of a novel human immune globulin subcutaneous, 20%: a Phase 2/3 study in Europe in patients with primary immunodeficiencies. (18th October 2016) - Borte, M.; Kriván, G.; Derfalvi, B.; Maródi, L.; Harrer, T.; Jolles, S.; Bourgeois, C.; Engl, W.; Leibl, H.; McCoy, B.; Gelmont, D.; Yel, L.
Summary: A highly concentrated (20%) immunoglobulin (Ig)G preparation for subcutaneous administration (IGSC 20%), would offer a new option for antibody replacement therapy in patients with primary immunodeficiency diseases (PIDD). The efficacy, safety, tolerability and pharmacokinetics of IGSC 20% were evaluated in a prospective trial in Europe in 49 patients with PIDD aged 2–67 years. Over a median of 358 days, patients received 2349 IGSC 20% infusions at monthly doses equivalent to those administered for previous intravenous or subcutaneous IgG treatment. The rate of validated acute bacterial infections (VASBIs) was significantly lower than 1 per year (0·022/patient‐year, P  < 0·0001); the rate of all infections was 4·38/patient‐year. Median trough IgG concentrations were ≥ 8 g/l. There was no serious adverse event (AE) deemed related to IGSC 20% treatment; related non‐serious AEs occurred at a rate of 0·101 event/infusion. The incidence of local related AEs was 0·069 event/infusion (0·036 event/infusion, when excluding a 13‐year‐old patient who reported 79 of 162 total related local AEs). The incidence of related systemic AEs was 0·032 event/infusion. Most related AEs were mild, none were severe. For 64·6% of patients and in 94·8% of IGSC 20% infusions, no local related AE occurred. The median infusion duration was 0·95 (range = 0·3‐4·1) h using mainly one to two administration sites [median = 2 sites (range = 1–5)]. Almost all infusions (99·8%) were administered without interruption/stopping or rate reduction. These results demonstrate that IGSC 20% provides an effective and well‐tolerated therapy for patients previously on intravenous or subcutaneous treatment, without the need for dose adjustment. Abstract : In 94.8% of IGSC 20% infusions (n=2338) administered to patients with PIDD in this European study, no causally related local AE occurred. Higher infusion rates or infusion volumes per site were not associated with an increased incidence of causally related local AEs. IGSC 20% provided an effective and well‐tolerated therapy for patients previously on intravenous or subcutaneous treatment, with no dose adjustment.